Toxoplasma gondii in semen of experimentally infected swine - Moura, Anderson B. [UNESP]; Costa, Alvimar J. [UNESP]; Jordão Filho, Sérgio [UNESP]; Paim, Beatriz B. [UNESP]; Pinto, Fernanda R. [UNESP]; Di Mauro, Daniela C. [UNESP] (FapUNIFESP (SciELO), 2007)
Eight reproductive boars were divided into three groups and inoculated with Toxoplasma gondii [GI (n=3) 1.5×104 oocysts strain P; GII (n=3) 1.0×106 tachyzoites strain RH; and GIII (n=2) non-inoculated control]. Clinical, hematological, parasitemia and serological tests and studies of the parasite in the semen through bioassay and PCR, and in reproductive organs (Bioassay and immunohistochemical analyses) were conducted to evaluate the toxoplasmic infection. Blood and semen were collected on day -2, -1, 1, 3, 5, 7, 9, 11, 14 and weekly up to 84 days post-inoculation (DPI). No clinical or hematimetric alteration was observed in the boars. Parasitemia was detected in one boar inoculated with oocysts at the 7th DPI and in another boar infected with tachyzoites (GII) at the 3rd and 49 th DPI. Serological tests revealed antibodies against T. gondii in animals inoculated with oocysts or tachyzoites at the 7th DPI with dilutions of 1:256 and 1:64, which reached peaks of 1:4096 at day 11 and 9, respectively. The bioassays revealed the presence of the parasite in semen samples of a boar inoculated with oocysts (GI) at 3, 49 and 56 DPI and from two boars infected with tachyzoites (GII), one animal at 5 and two animals at 49 days DPI. Mice inoculated with semen from the control group (GIII) remained serologically negative. PCR analysis showed T. gondii DNA in the semen of Boar 1 and Boar 3 inoculated with tachyzoites and oocysts, respectively. The immunohistochemical tests showed T. gondii in the reproductive organs of Boar 1 and Boar 2, inoculated with tachyzoites and oocysts, respectively. These findings suggest the possible occurrence of venereal transmission of T. gondii in swine.
Keywords: Bioassays; PCR; Semen; Swine; Toxoplasmosis; Animalia; Mus; Suidae; Toxoplasma gondii